Integrating wireless technology in the enterprise - Wheeler, William (William R.) (Amsterdam ; Boston : Digital Press, 2004)
Integrating Wireless Devices in the Enterprise provides a solution that every enterprise can use, described in terms of scope, feasibility and return on investment, architecture, and data structures. The solution Wheeler offers here is scalable from a single handheld and single desktop to small workgroup to large enterprise environments. The number of devices is not a determinant of success or failure. It's more often the planning and managing of them that's crucial. This book also provides tools to deal with the increase of devices, and the corresponding complexity of managing those resources and the increase in cost to the firm. *Synchronize networked data with the mobile device fleet *Synchronize a mobile device with networked data that is mission critical *Connect any device to any data source, over any network.
Includes bibliographical references (p. 353-360) and index.
Keywords: Wireless communication systems; Electronic books